A Comparative Analysis of Research and Development Activities in Poland and the Czech Republic in the Years 2006–2014 - Zygmunt, Aleksandra; Malátek, Vojtěch (Regional Barometer. Analyses & Prognoses, 2018)
Contemporary economies and regions face the necessity to adaptation to changes in the environment. In this respect, an important role plays innovation, with R&D activities as a key determinant of maintaining and enhancing competitive advantage. The aim of the article is a comparative analysis of research and development activities in Poland and the Czech Republic. At first, it was made considerations about the importance of innovation in maintaining and enhancing the competitiveness of economies and regions. In this respect, the special emphasis was put on R&D activities. Next, on the base on time series analysis, selected aspects of R&D activities in Poland and the Czech Republic in the years 2006–2014 were compared. In analyses information from the European Statistical Office were used. The results of the research indicate a relatively high dissonance between Poland and the Czech Republic in terms of the analyzed variables. Compared to Poland, the Czech economy stands out with a significantly higher adjustment of R&D activities. The added value of the article is to highlight the diversity of research and development activities between EU countries with a similar level of innovation. The key value of the article is also the underlining of the impact of R&D activities on the competitiveness of economies and regions.